Money for Nothing? Financing the 2016 and 2020 U.S. Presidential Nomination Campaigns - Turek, Maciej (Political Preferences, 2020)
The aim of the paper is to analyze the relationship between campaign money and winning the 2016 and 2020 presidential nominations in the United States. While in the last two decades of the twentieth century candidates who raised most money almost always became major party nominees, the record is mixed for presidential cycles 2004-2012. By comparing various dimensions of campaign finance, including activities of candidates' campaign committees and outside groups, the Author demonstrates that while successful fundraising, resulting in dozens of millions of dollars at the disposal of candidates, seems necessary to run a competitive campaign, raising the most money is no longer pre-requisite for becoming major party presidential nominee.